2008
DOI: 10.1111/j.1601-183x.2008.00414.x
|View full text |Cite
|
Sign up to set email alerts
|

Methyl‐CpG‐binding protein 2 polymorphisms and vulnerability to autism

Abstract: The methyl-binding protein gene, MECP2, is a candidate for involvement in autism through its implication as a major causative factor in Rett syndrome that has similarities to autism. Rare mutations in MECP2 have also been identified in autistic individuals. We have examined the possible broader involvement of MECP2 as a predisposing factor in the disorder. Analysis of polymorphic markers spanning the gene and comprising both microsatellites and single nucleotide polymorphisms (SNPs) by the transmission disequi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 35 publications
0
44
0
Order By: Relevance
“…Reduced MECP2 expression in autistic patients has been associated with increased MECP2 promoter DNA methylation (Nagarajan et al 2006(Nagarajan et al , 2008. Moreover, MECP2 mutations within the coding regions (Carney et al 2003;Beyer et al 2002;Lam et al 2000;Loat et al 2008) and sequence variants within the MECP2 3′UTR (Shibayama et al 2004;Coutinho et al 2007) are also found in autistic patients, indicating the potential involvement of these sequence variations in altered expression of MECP2 in autism. Not only reduced MECP2 expression, but also overexpression of MECP2 is found in ASD patients (Kuwano et al 2011).…”
Section: Mecp2 and Other Human Diseases Autism Spectrum Disordersmentioning
confidence: 91%
“…Reduced MECP2 expression in autistic patients has been associated with increased MECP2 promoter DNA methylation (Nagarajan et al 2006(Nagarajan et al , 2008. Moreover, MECP2 mutations within the coding regions (Carney et al 2003;Beyer et al 2002;Lam et al 2000;Loat et al 2008) and sequence variants within the MECP2 3′UTR (Shibayama et al 2004;Coutinho et al 2007) are also found in autistic patients, indicating the potential involvement of these sequence variations in altered expression of MECP2 in autism. Not only reduced MECP2 expression, but also overexpression of MECP2 is found in ASD patients (Kuwano et al 2011).…”
Section: Mecp2 and Other Human Diseases Autism Spectrum Disordersmentioning
confidence: 91%
“…see Craig, 2007). In the context of our observations of the CAST measures, it is of interest to note that Laumonnier et al (2007) have highlighted the high proportion of postsynaptic signaling complexes, coded for by genes on the X chromosome, that have a strong association with mental retardation and with autism spectrum disorders in particular, and further, that variants in MECP2 (X-linked) have been recently shown to be associated with vulnerability to autism (Loat et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Rett syndrome is caused by mutations in the methyl-CpG binding protein 2 (MeCP2), which binds to me CpG islands throughout the chromosomes (43). As abnormal mitochondria and mitochondrial function have been reported in several Rett patient studies, loss of MeCP2 might disrupt the coordinate regulation of nDNA energy gene expression (10).…”
Section: Energy Fluctuation and Cyclic Adaptationmentioning
confidence: 99%